How Green Organizational Strategy and Environmental CSR Affect Organizational Sustainable Performance Through Green Technology Innovation Amid COVID-19 - Ye, Maoran; Hao, Feng; Shahzad, Mohsin; Kamran, Hafiz Waqas (Frontiers in Environmental Science, 2022)
The growth of green-oriented businesses for sustainable development (SD) is no longer an option in the current dynamic world, especially for manufacturing businesses in general. Following the same, the present study investigates the interlinkages between green organizational strategy (GOS), environmental corporate social responsibility (ECSR), and organizational sustainable performance (OSP) by exploring the key mediating role of green technology innovation (GTI). This study uses a quantitative method to gather data from Chinese manufacturing industries, employing a well-structured questionnaire. Senior and middle-level managers were the intended responders. From the primary survey, 264 valid responses were gathered. The final data was analyzed using SmartPLS (ver 3.3.9) by adopting structural equation modeling (SEM) to examine the associations between targeted constructs, and it adds to the recent literature by offering a cohesive model of GOS, ECSR, GTI, and OSP. The findings revealed that GOS has a strong positive effect on ECSR, GTI, and OSP. Further, ECSR has a strong positive impact on GTI and OSP. Meanwhile, GTI has a key mediating variable in these relationships, which previous studies have not explored. The study innovatively integrates the three green traits into a comprehensive model that is understudied in existing literature, such as GOS, ECSR, and GTI, to help businesses improve their sustainable competitive advantage. We help you improve your environmental performance and achieve solid sustainability over the long term.